Evaluasi Pengendalian Internal pada Rekam Medis Elektronik Rumah Sakit Hermina Pasteur menggunakan COSO Internal Control Integrated Framework dan COBIT 2019 Maturity Model - Gwendry Ramadhany; Amelia Setiawan; Miriam Renee Maengkom (AKADEMIK: Jurnal Mahasiswa Ekonomi & Bisnis, 2026)
The growing reliance on Electronic Health Records (EHR) in Indonesian hospitals raises concerns over data security, especially after recent national incidents highlighting vulnerabilities in public information systems. Hermina Pasteur Hospital, as part of a digitally integrated hospital network, must ensure that its internal controls adequately protect patient data and support reliable service delivery. This study aims to evaluate the effectiveness of internal controls governing the hospital’s EHR using the COSO Internal Control Integrated Framework and the COBIT 2019 Maturity Model. A sequential explanatory mixed-methods design was applied, combining quantitative assessments through a COSO-based questionnaire with qualitative insights from observations and interviews with key personnel. The integration of both approaches allowed for a more grounded interpretation of control practices and their implementation. The findings show that the hospital’s EHR controls are at the “Managed” maturity level, where several procedures are in place but not yet fully standardized or consistently documented. Strengths were observed in risk assessment, whereas weaknesses appeared mainly in control activities and accountability practices. These results indicate that improvements in control environment, documentation practices, and monitoring mechanisms are necessary to strengthen the overall reliability of EHR governance.